Association of Clonal Hematopoiesis of Indeterminate Potential with Worse Kidney Function and Anemia in Two Cohorts of Patients with Advanced Chronic Kidney Disease. Issue 5 (May 2022) - Vlasschaert, Caitlyn; McNaughton, Amy J.M.; Chong, Michael; Cook, Elina K.; Hopman, Wilma; Kestenbaum, Bryan; Robinson-Cohen, Cassianne; Garland, Jocelyn; Moran, Sarah M.; Paré, Guillaume; Clase, Catherine M.; Tang, Mila; et al.
Significance Statement: Clonal hematopoiesis of indeterminate potential (CHIP), a premalignant expansion of clonal leukocytes caused by acquired somatic mutations in myeloid stem/progenitor cells, occurs in 10%–15% of the general population aged 65 years or older. This proinflammatory condition appears causally associated with cardiovascular disease and death. The authors found that 43 of 172 (25%) individuals with advanced CKD had CHIP. Those with CHIP had a 2.2-fold greater risk of kidney failure over 5 years of follow-up and were more likely to have complications of CKD (including anemia) compared with those without CHIP. More research, including studies in animal models, is needed to understand the relationship between CHIP and CKD. CHIP-related inflammation might offer a novel therapeutic target for those with CHIP and CKD. Visual Abstract: Abstract : Background: Clonal hematopoiesis of indeterminate potential (CHIP) is an inflammatory premalignant disorder resulting from acquired genetic mutations in hematopoietic stem cells. This condition is common in aging populations and associated with cardiovascular morbidity and overall mortality, but its role in CKD is unknown. Methods: We performed targeted sequencing to detect CHIP mutations in two independent cohorts of 87 and 85 adults with an eGFR<60 ml/min per 1.73m 2 . We also assessed kidney function, hematologic, and mineral bone disease parameters cross-sectionally at baseline, and collected creatinine measurements over the following 5-year period. Results: At baseline, CHIP was detected in 18 of 87 (21%) and 25 of 85 (29%) cohort participants. Participants with CHIP were at higher risk of kidney failure, as predicted by the Kidney Failure Risk Equation (KFRE), compared with those without CHIP. Individuals with CHIP manifested a 2.2-fold increased risk of a 50% decline in eGFR or ESKD over 5 years of follow-up (hazard ratio 2.2; 95% confidence interval, 1.2 to 3.8) in a Cox proportional hazard model adjusted for age, sex, and baseline eGFR. The addition of CHIP to 2-year and 5-year calibrated KFRE risk models improved ESKD predictions. Those with CHIP also had lower hemoglobin, higher ferritin, and higher red blood cell mean corpuscular volume versus those without CHIP. Conclusions: In this exploratory analysis of individuals with preexisting CKD, CHIP was associated with higher baseline KFRE scores, greater progression of CKD, and anemia. Further research is needed to define the nature of the relationship between CHIP and kidney disease progression.